Determination of vibration characteristics of blades of gas turbine engines contactless method - Кучер, О.Г.; Харитон, В.В. (Proceedings of National Aviation University (archive), 2007)
Non-contact method simulation for blade real-time dynamic behavior determination is presented. This method uses eddy-current, capacitance or optical probes for blade tip deflections measurements which are related with time of blade tip passing trough the probe.